Hubungan Perfeksionis dan Prokrastinasi Akademik Mahasiswa yang Sedang Menyusun Skripsi di Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember - Nurmaidah, Siti; Fitriani, Aprilya (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2024)
Thesis is an essential requirement for graduation and the attainment of a bachelor's degree  (S1). Throughout the thesis-writing process, students inevitably encounter various obstacles. These challenges may lead students to engage in academic procrastination, influenced in part by perfectionist tendencies. Perfectionism can prompt students to set unrealistic standards, resulting in procrastination as they strive to meet these standards. This study aims to investigate the relationship between perfectionism and academic procrastination among final-year students working on their thesis at the Faculty of Da'wah, KH Ahmad Siddiq Jember State Islamic University. Employing a quantitative approach with correlational research, the study utilizes simple random sampling, surveying 148 students. Data analysis is conducted using Pearson product moment correlation with SPSS 25.0 software. The findings reveal a moderate positive correlation (r = 0.413) between perfectionism and academic procrastination (p < 0.05). Thus, the study concludes that perfectionism significantly contributes to academic procrastination among final-year students, highlighting the impact of idealistic beliefs on students' thesis preparation.